Pengaruh Harga, Lokasi dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Syanda Cell & Agen Brilink Sidomulyo Kecamatan Pulau Rakyat Kabupaten Asahan - Riska Ariyanti; Neni Triastuti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Customer satisfaction is an essential factor in maintaining business sustainability in the retail and financial service sector, particularly for Syanda Cell & Agen Brilink Sidomulyo located in Pulau Rakyat District Asahan Regency. The aim of this study is to analyze the influence of price, location, and service quality on customer satisfaction at Syanda Cell & Agen Brilink Sidomulyo. This study uses a quantitative approach with an associative method. The sample consisted of 96 respondents determined using Wibisono formula with incidental sampling technique. Data were collected through Likert-scale questionnaires and processed using SPSS version 27. Data analysis was conducted using multiple linear regression. The results showed that price, location, and service quality simultaneously and partially have a positive and significant effect on customer satisfaction. Service quality was identified as the most dominant factor influencing customer satisfaction. Therefore, improving pricing strategy, strategic location, and service quality can increase customer satisfaction and strengthen customer loyalty at Syanda Cell & Agen Brilink Sidomulyo. These findings imply that managers should prioritize competitive pricing, accessible location, and improved service quality to enhance customer satisfaction and encourage repeat purchase behavior in the competitive retail and banking agent service environment in the study area of Asahan Regency North Sumatra Indonesia context.